Urinary Retention and Air in the Spinal Canal; a Case Report - Karimian, Hoda; Gheiratian, Mohammadmahdi (Archives of Academic Emergency Medicine, 2018)
Cauda equina syndrome (CES) although uncommon, is a very serious condition, which should be diagnosed as soon as possible.Â  Urinary dysfunction following a lumbosacral trauma is a key for the physician to consider CES as the most probable diagnosis. Up to 62% of CES patients report a recent episode of trauma. We herein report a young man with CES due to sacral fracture with an interesting imaging.